Host range of Exallomochlus hispidus (Morrison) (Hemiptera: Pseudococcidae) in West Java, Indonesia. Issue 2 (July 2021) - Indarwatmi, M; Nasution, I A; Sasmita, H I; Ernawan, B; Ratna, E S; Sartiami, D; Arinana; Sulaeha; Maharani, Y
Abstract: Exallomochlus hispidus (Morrison) (Hemiptera: Pseudococcidae) is a polyphagous mealybug with a wide host range. Many of them are fruits that have high economic value and potential export commodities. In addition, E. hispidus is a quarantine pest so that its presence can be an export barrier. The purposive sampling method were used to take plant samples. Host plants were sampled in 4 districts in Bogor, Sukabumi, Purwakarta, and Garut, West Java. Mealybugs and their host plants were put in a paper bag and taken to the laboratory. Adult female mealybugs were prepared microscopically for identification. Results showed that E. hispidus was found on 31 species of 18 families. Most of the hosts were fruit crops 54.84% and at least medicinal plant and weed 3.23%. The major host plants are fruit crops including cocoa, duku, rambutan, sapodilla, soursop, mangosteen and lemon. The part of the plant which is inhabited by E. hispidus mostly is on the fruit and the least on the stem. The results of this study were expected to provide information on the host range of E. hispidus so that it can be prevented from spreading and proper control is taken.